Modeling the impact of corporate legitimacy on tax compliance intention to small and medium-sized enterprises - David Amani (Cogent Business & Management, 2024)
The objective of this study was to determine the effect of corporate legitimacy on tax compliance intentions among small and medium-sized enterprises (SMEs) in Tanzania. This study is among a few that explore the issue of tax avoidance and leakages in sub-Saharan Africa through the lens of corporate legitimacy. The research seeks to contribute to ongoing efforts in sub-Saharan Africa aimed at reducing tax avoidance and leakages. The study formulates and assesses a conceptual model that explores the relationship between corporate legitimacy, public trust, and tax compliance intentions. Data was collected through a cross-sectional survey of 430 SMEs operating in the tourism industry. The analysis was carried out using structural equation modeling and the results showed that corporate legitimacy influences tax compliance intentions through public trust. The study recommends that tax authority managers consider taxpayers' legitimacy as a strategic approach to combat tax avoidance and leakages.
Keywords: 650; Corporate legitimacy; public trust; tax compliance intention; small and medium-sized enterprises